Exotoxin targeted drug modalities - Laisi, Arttu (My University, 2021)
According to World Health Organization (WHO), antimicrobial resistance is one of the major global health issues to track in 2021. As the efficiency of current antibiotics have gradually been declining for several decades due to the deteriorating resistance status, the demands to develop new potential antimicrobial drugs have increased rapidly. Bacterial virulence factors are molecules that enhances the probability of the pathogen to cause disease in a host. With antivirulence drugs, bacteria are not killed, but specifically disarmed by neutralizing their virulence factors, thus exposing pathogens to the influence of immunological defense mechanisms. In use of pathogen specific antivirulence drugs, the selective pressure for resistance is believed to be reduced since the drugs don’t directly have an effect on bacterial viability. Exotoxins are an extensive group of bacterial proteins, which can damage the host cells by disrupting physiological cellular functions, or directly destroy host cells, e.g. via cell lysis. Exotoxins have a significant role in bacterial pathogenicity and in some infectious diseases, e.g. cholera, tetanus and botulism, bacterial exotoxins act as the primary disease-causing virulence factor and are therefore ideal targets for antivirulence drugs. In this review article, we focus on drug modalities, which target bacterial exotoxins. We describe how the different drug modalities work and review the key pre-clinical and clinical trial data that has led to the approval of currently used exotoxin-targeted drugs: Raxibacumab (Abthrax®), obiltoxaximab (Anthim®) and bezlotoxumab (Zinplava®). We also go through the advantages and disadvantages of these modalities and highlight the recent outcomes from preclinical and clinical trials of potential exotoxin-targeting drug molecules. The manuscript of this review article has been sent to be peer reviewed and published in ACS Infectious Diseases.